Assay for Pathogen-Associated Molecular Pattern (PAMP)-Triggered Immunity (PTI) in Plants - Chakravarthy, Suma (MyJove Corporation, 2009)
To perceive potential pathogens in their environment, plants use pattern recognition receptors (PRRs) present on their plasma membranes. PRRs recognize conserved microbial features called pathogen-associated molecular patterns (PAMPs) and this detection leads to PAMP-triggered immunity (PTI), which effectively prevents colonization of plant tissues by non-pathogens(1,2). The most well studied system in PTI is the FLS2-dependent pathway(3). FLS2 recognizes the PAMP flg22 that is a component of bacterial flagellin. Successful pathogens possess virulence factors or effectors that can suppress PTI and allow the pathogen to cause disease(1). Some plants in turn possess resistance genes that detect effectors or their activity, which leads to effector-triggered immunity (ETI)(2). We describe a cell death-based assay for PTI modified from Oh and Collmer(4). The assay was standardized in N. benthamiana, which is being used increasingly as a model system for the study of plant-pathogen interactions(5). PTI is induced by infiltration of a non-pathogenic bacterial strain into leaves. Seven hours later, a bacterial strain that either causes disease or which activates ETI is infiltrated into an area overlapping the original infiltration zone. PTI induced by the first infiltration is able to delay or prevent the appearance of cell death due to the second challenge infiltration. Conversely, the appearance of cell death in the overlapping area of inoculation indicates a breakdown of PTI. Four different combinations of inducers of PTI and challenge inoculations were standardized (Table 1). The assay was tested on non-silenced N. benthamiana plants that served as the control and plants silenced for FLS2 that were predicted to be compromised in their ability to develop PTI.